2014
DOI: 10.3906/tar-1307-108
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast DNA variation and pollen contamination in a Pinus brutia Ten. clonal seed orchard: implication for progeny performance in plantations

Abstract: Pollen contamination is one of the important factors affecting the yield, adaptability, and genetic quality of the seed produced from seed orchards in forest tree breeding programs. Incoming pollen from the forests surrounding the seed orchard is a major concern in tree breeding because it contributes to losses in the expected genetic gains from seed orchard crops. The genetic variation and the level of pollen contamination in a 16-year-old Pinus brutia Ten. first-generation clonal seed orchard was studied usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…These contamination values are within the range recorded in the literature for both wind and insect pollinated orchards. Bilgen & Kaya (2014) reported that 29% of the embryos of Pinus brutia were sired by pollen sources outside the orchard. Feng et al (2010), Torimaru et al (2009) and Buiteveld et al (2001) estimated contamination rates of 25%, 51% and 70% for Pinus koraiensis, Pinus silvestris, and Quercus robus, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These contamination values are within the range recorded in the literature for both wind and insect pollinated orchards. Bilgen & Kaya (2014) reported that 29% of the embryos of Pinus brutia were sired by pollen sources outside the orchard. Feng et al (2010), Torimaru et al (2009) and Buiteveld et al (2001) estimated contamination rates of 25%, 51% and 70% for Pinus koraiensis, Pinus silvestris, and Quercus robus, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Failures in the recognition of parental trees within the studied orchard can be explained by: (i) natural regeneration of individuals from outside (e.g., seeds carrying unrelated genotypes) establishing within the clonal orchard; (ii) mutational events (such as inversions) in the offspring, whose rate is fairly high in SSR regions of the genome; (iii) scoring mistakes; and (iv) pollen flow from outside the orchard (Plomion et al 2001, Bilgen & Kaya 2014. Some of these causes can be easily ruled out in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen contamination influences the genetic worth of seed orchard and therefore determines the quality of seed production, which may include reduction of genetic gain (Grattapaglia et al 2014, Funda et al 2016, Gonzaga et al 2016). Studies of wind-pollinated orchards show that between 25 and 80% of seeds produced usually result from pollen contamination (Kaya et al 2006, Torimaru et al 2009, Bilgen & Kaya 2014. In young orchards, where pollen production is limited, the contamination rate could be even higher.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic markers (biochemical and molecular) have been used to determine mating system parameters and estimate pollen contamination in seed orchards (Fernandes et al 2008, Torimaru et al 2009, Feng et al 2010, Kaya & Isik 2010, Bilgen & Kaya 2014. Biochemical markers such as allozymes were popularly used in the 1980s and 1990s because they are easy to use, cost effective and exhibit simple Mendelian inheritance (Firas et al 2015).…”
Section: Introductionmentioning
confidence: 99%